Risk Is Relative: Heterogeneous Responses to Institutional Risks for Foreign Investment - Beazer, Quintin; Blake, Daniel J. (Oxford University Press, 2021)
Are economic actors equally sensitive to institutional conditions? While existing research recognizes that institutions can have varying effects on actors' interests,the implicit assumption is that actors are homogeneous in how sensitive they are to their institutional environment. We investigate this assumption in the context of foreign direct investment,arguing that actors from countries with weaker institutions will be less affected by information about host country institutional conditions-both good and bad. We test this argument using survey data from a diverse group of managers-in-training at an international business school. We find that when asked to evaluate a potential foreign investment location,respondents from developing countries are significantly less sensitive to information about the host country's courts than their counterparts from developed economies. In contrast,we find that economic actors from both developed and developing countries respond similarly to information about the stability of economic policies. The findings suggest that sensitivity to the risks and safeguards of certain institutional conditions vary systematically across actors,depending on both the home environment to which economic actors have been exposed and the type of host institution. © 2021 The Author. Published by Oxford University Press on behalf of the International Studies Association.
Keywords: capital market; economic policy; financial system; foreign direct investment; institutional framework; research work